Newborn screening for X-linked adrenoleukodystrophy in Italy: Diagnostic algorithm and disease monitoring - Bonaventura, Eleonora; Alberti, Luisella; Lucchi, Simona; Cappelletti, Laura; Fazzone, Salvatore; Cattaneo, Elisa; Bellini, Matteo; Izzo, Giana; Parazzini, Cecilia; Bosetti, Alessandra; Di Profio, Elisabetta; Fiore, Giulia; et al. (Frontiers in Neurology, 2023)
Introduction X-linked adrenoleukodystrophy (X-ALD) is the most common inherited peroxisomal disorder caused by variants in the ABCD1 gene. The main phenotypes observed in men with X-ALD are primary adrenal insufficiency, adrenomyeloneuropathy, and cerebral ALD (cALD). Cerebral ALD consists of a demyelinating progressive cerebral white matter (WM) disease associated with rapid clinical decline and is fatal if left untreated. Hematopoietic stem cell transplantation is the standard treatment for cALD as it stabilizes WM degeneration when performed early in the disease. For this reason, early diagnosis is crucial, and several countries have already implemented their newborn screening programs (NBS) with the assessment of C26:0-lysophosphatidylcholine (C26:0-LPC) values as screening for X-ALD. Methods In June 2021, an Italian group in Lombardy launched a pilot study for the implementation of X-ALD in the Italian NBS program. A three-tiered approach was adopted, and it involved quantifying the values of C26:0-LPC and other metabolites in dried blood spots with FIA-MS/MS first, followed by the more specific ultra-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) technique and, finally, the genetic confirmation via focused NGS. Discussion Genetically confirmed patients are set to undergo a follow-up protocol and are periodically evaluated to promptly start a specific treatment if and when the first signs of brain damage appear, as suggested by international guidelines. A specific disease monitoring protocol has been created based on literature data and personal direct experience. Conclusion The primary aim of this study was to develop a model able to improve the early diagnosis and subsequent follow-up and timely treatment of X-ALD. Ethics The study was approved by the local ethics committee. The research was conducted in the absence of any commercial or financial relationship that could be construed as a potential conflict of interest.